Narrativas de favela e identidades negras: Carolina Maria de Jesus e Conceição Evaristo - Margarete Aparecida de Oliveira (2015)
This thesis aims to study the Afro-Brazilian narratives 'Quarto de Despejo: diário de uma favelada', by Carolina Maria de Jesus, and 'Becos da memória', whose author is Conceição Evaristo. In order to analyze the discourses produced by these intellectual women of african-descent, it seeks to verify the representation of otherness in these narratives concerning the issues of memory, identity, violence, strength and the living conditions of black people living in urban areas, specifically in the slums. The thesis intends to demonstrate how the historical content of Brazilian modernity is articulated in these texts, as well as to reflect on the position of the Afro-Brazilian writer regarding the canonical production and its critical importance.